Amplified fluorescence detection of adenosine via catalyzed hairpin assembly and host–guest interactions between β-cyclodextrin polymer and pyrene. Issue 8 (21st March 2016) - Huang, Haihua; Yang, Xiaohai; Wang, Kemin; Wang, Qing; Guo, Qiuping; Huang, Jin; Liu, Jianbo; Song, Chunxia
Abstract : We introduce an enzyme-free amplified detection strategy for the small molecule adenosine. Abstract : Nowadays, enzyme-free nucleic acid-based signal amplification strategies are frequently utilized in the design of biosensors due to their excellent sensitivity. Developing more extended analytical methods is fundamental for basic studies in the biological and biomedical fields. Herein, we introduce an enzyme-free amplified detection strategy for the small molecule adenosine. The approach is based on adenosine–aptamer binding triggered catalyzed hairpin assembly and host–guest interactions between β-cyclodextrin polymer (β-CDP) and pyrene. Two hairpin probes (probe H1 and probe H2) and an aptamer-trigger/inhibitor duplex probe were employed in the system and the pyrene-labeled probe H1 was chosen as the signal unit. In the absence of adenosine, the aptamer-trigger was inhibited by the inhibitor strand. The hairpin probes were in the closed hairpin formation without activation of the trigger strand. Pyrene labeled at the 5′-termini of the single-stranded stem of probe H1 could be easily trapped in the hydrophobic cavity of β-CDP because of weak steric hindrance, leading to a significant fluorescence enhancement. Once the hairpin assembly was catalyzed by the adenosine–aptamer binding event, a hybridized DNA duplex H1/H2 was created continuously. Pyrene labeled at the 5′-termini of the DNA duplex H1/H2 finds it difficult to enter the cavity of β-CDP due to steric hindrance, leading to a weaker fluorescence signal. Thus, the target could be detected by this simple mix-and-detect amplification method without a need for expensive and perishable protein enzymes. As low as 42 nM of adenosine was detected by this assay, which is comparable to that of some reported colorimetric methods. Meanwhile, the proposed method was further successfully applied to detect adenosine in human serum samples, showing great potential for adenosine detection from complex fluids.